FFA VMS: satellite surveillance of Pacific tuna fisheries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Andrew Richards outlines how the satellite-based vessel monitoring system (VMS) of the South Pacific Forum Fisheries Agency (FFA) is substantially benefiting local fishermen and the tuna industry in the Pacific. The FFA VMS is primarily used to ensure tha